Tuning Surface Properties of Low Dimensional Materials via Strain Engineering. Issue 30 (4th July 2016) - Yang, Shengchun; Liu, Fuzhu; Wu, Chao; Yang, Sen
Abstract : The promising and versatile applications of low dimensional materials are largely due to their surface properties, which along with their underlying electronic structures have been well studied. However, these materials may not be directly useful for applications requiring properties other than their natal ones. In recent years, strain has been shown to be an additionally useful handle to tune the physical and chemical properties of materials by changing their geometric and electronic structures. The strategies for producing strain are summarized. Then, the electronic structure of quasi‐two dimensional layered non‐metallic materials (e.g., graphene, MX2, BP, Ge nanosheets) under strain are discussed. Later, the strain effects on catalytic properties of metal‐catalyst loaded with strain are focused on. Both experimental and computational perspectives for dealing with strained systems are covered. Finally, an outlook on engineering surface properties utilizing strain is provided. Abstract : Strain is a promising handle to tune the surface properties of low dimensional materials . Firstly, four approaces to introduce strain to these materials are briefly summarized. Then the effects of strain on the electronic properties of layered materials and catalytic properties of nanoparticles are presented in detail. Finally, the challenges for the practical applications of strain engineering are also highlighted.